Colour and quality characteristics of canned pineapple slices. - Kanniah, Jayashree; Ahmad, Siti Hajar; Osman, Azizah; Tengku Muda Mohamed, Mahmud (2001)
Three grades of canned pineapple slices were evaluated for their colour, SSC, syrup density and flesh firmness. Can vacuum and headspace were also determined. Fancy grade of canned pineapple slices had significantly lower L* and h 0 but higher C* values resulting in distinct golden yellow colour of the slices. Standard grade, which was significantly higher in L* and h 0 but lower in C* values, had a pale yellow colour. There was a significant decrease in flesh firmness with changes in flesh colour from pale yellow (Standard grade) to golden yellow (Fancy grade). The values of SSC and syrup density for Fancy grade were significantly higher compared to Standard and Choice grades. This was expected since Fancy consisted of full-ripe pineapple fruit with higher SSC compared to the other grades. Results of can vacuum were according to product specifications but can headspace and syrup density values did not meet product specifications. The Malaysian Standard specifications for canned pineapple need to be revised.